Zero fail : the rise and fall of the Secret Service - Leonnig, Carol (Random House, 2021)
"Carol Leonnig has been covering the Secret Service for The Washington Post for most of the last decade, bringing to light the gaffes and scandals that plague the agency today--from a toxic work culture to outdated equipment and training to the deep resentment among the ranks with the agency's leadership. But the Secret Service wasn't always so troubled. The Secret Service was born in 1865, in the wake of the assassination of Abraham Lincoln, but its story begins in earnest in 1963, with the death of John F. Kennedy. Shocked into reform by their failure to protect the president on that fateful day, this once-sleepy agency was rapidly transformed into a proud, elite unit that would finally redeem themselves in 1981 by valiantly thwarting an assassination attempt against Ronald Reagan. But this reputation for courage and efficiency would not last forever. By Barack Obama's presidency, the Secret Service was becoming notorious for break-ins at the White House, an armed gunman firing at the building while agents stood by, a massive prostitution scandal in Cartagena, and many other dangerous lapses. To expose these shortcomings, Leonnig interviewed countless current and former agents who risked their careers to speak out about an agency that's broken and in desperate need of a reform"--